Review of levetiracetam, with a focus on the extended release formulation, as adjuvant therapy in controlling partial-onset seizures - Carol M Ulloa (Dove Medical Press, 2009)
Carol M Ulloa, Allen Towfigh, Joseph SafdiehDepartment of Neurology and Neuroscience, Weill Medical College of Cornell University, New York, NY, USAAbstract: Levetiracetam is a second-generation antiepileptic drug (AED) with a unique chemical structure and mechanism of action. The extended release formulation of levetiracetam (Keppra XR™; UCB Pharma) was recently approved by the Food and Drug Administration for adjunctive therapy in the treatment of partial-onset seizures in patients 16 years of age and older with epilepsy. This approval is based on a double-blind, randomized, placebo-controlled, multicenter, multinational trial. Levetiracetam XR allows for once-daily dosing, which may increase compliance and, given the relatively constant plasma concentrations, may minimize concentration-related adverse effects. Levetiracetam’s mode of action is not fully elucidated, but it has been found to target high-voltage, N-type calcium channels as well as the synaptic vesicle protein 2A (SV2A). Levetiracetam has nearly ideal pharmacokinetics. It is rapidly and almost completely absorbed after oral ingestion, is ‹10% protein-bound, demonstrates linear kinetics, is minimally metabolized through a pathway independent of the cytochrome P450 system, has no significant drug–drug interactions, and has a wide therapeutic index. The most common reported adverse events with levetiracetam XR were somnolence, irritability, dizziness, nausea, influenza, and nasopharyngitis. Levetiracetam XR provides an efficacious and well-tolerated treatment option for adjunctive therapy in the treatment of partial-onset seizures.Keywords: levetiracetam, partial-onset seizures, antiepileptic drugs